Um método de ensino para o uso de metáforas no projeto da interação - Gonçalves, Anderson Cavalcante (2014)
The use of metaphors in interaction design contributes to the interfaces that are simple and intuitive. However, it is not easy for students to learn how to use metaphors. It is a complex task to teach students to develop interactive experiences through metaphors. This paper proposes a method for teaching the use of metaphors in interface design. The teaching method consists of a framework for preparation of exercises, and provocative questions related knowledge metáforas. The teaching method is used to propose designed to encourage interaction tasks, group learning and creativity of students. This paper presents six case studies, applied in different undergraduate classes at the Federal University of Goiás, where interactions between students were analyzed, creativity and experience of students in relation to the proposed teaching method.